Phase-evolution in high entropy alloys: Role of synthesis route. (June 2016) - Syed Ghazi, Sarwat; Ravi, K.R.
Abstract: Synthesis route can have a significant influence on the process of phase-choice and -evolution in High Entropy Alloys (HEAs). With the objective of instituting awareness, this communication on the foundation of phase diagrams, adopted using the CALPHAD approach, attempts at describing and deciphering the cause for such gradation. Graphical abstract: